The Mediterranean diet increases glucagon‐like peptide 1 and oxyntomodulin compared with a vegetarian diet in patients with type 2 diabetes: A randomized controlled cross‐over trial. Issue 6 (24th September 2020) - Di Mauro, Antonio; Tuccinardi, Dario; Watanabe, Mikiko; Del Toro, Rossella; Monte, Lavinia; Giorgino, Riccardo; Rampa, Lorenzo; Rossini, Giovanni; Kyanvash, Shadi; Soare, Andreea; Rosati, Milena; Piccoli, Alessandra; et al.
Abstract: Aim: To compare a Mediterranean diet (MED) with a high‐fibre vegetarian diet (HFV) in terms of hunger‐satiety perception through post‐prandial assessment of appetite‐related hormones glucagon‐like peptide 1 (GLP‐1) and oxyntomodulin, as well as self‐rated visual analogue scale (VAS) quantification, in overweight/obese subjects with type 2 diabetes (T2D). Materials and methods: Twelve T2D subjects (Male to female ratio = 7:5), mean age 63 ± 8.5 years, were enrolled in a randomized, controlled, crossover study. Participants consumed an MED meal as well as an isocaloric meal rich in complex carbohydrate as well as an isocaloric MED meal in two different visits with a 1‐week washout period between the two visits. Appetite ratings, glucose/insulin, and gastrointestinal hormone concentrations were measured at fasting and every 30' until 210' following meal consumption. Results: GLP‐1 and oxyntomodulin levels were significantly higher following MED meal compared with HFV meals (210' area under the curve, p < 0.022 and p < 0.023, respectively). Both MED and HFV meal resulted in a biphasic pattern of GLP‐1 and oxyntomodulin, although MED meal was related to a delayed, significantly higher second GLP‐1 peak at 150' compared with that of HFV meal ( p < 0.05). MED meal was related to lower glucose profile compared with HFV meal ( p < 0.039), whereas we did not observe significant changes in terms of self‐reported VAS scores and insulin trend. Conclusions: In T2D overweight/obese subjects, an MED meal is more effective than a HFV meal in terms of post‐prandial plasma glucose homoeostasis and GLP‐1 and oxyntomodulin release. These changes were not confirmed by VAS appetite self‐assessment over a 210' period.